Motivation and Vocabulary Learning: Increasing the Effectiveness of Teaching L2 Formulaic Sequences Through Motivational Strategies and Mental Imagery - Le Thi, Duyen (2019)
The primary concern of instructed SLA is how best to improve the efficacy of L2 teaching and learning at both specific and general levels. At specific levels such as vocabulary learning, a large body of literature has focused on examining relative effects of varying cognitive techniques on learning. However, no research has examined the effects of principled explicit instruction combined with incidental exposures relative to the coursebook-based teaching approach in terms of acquisition of formulaic sequences. At general levels, substantial research has provided evidence concerning factors other than cognitive ability such as metacognitive, social or motivational variables that contribute to overall language achievement. However, in the narrow realm of instructed L2 vocabulary learning, only a handful of studies have investigated how motivational dispositions facilitate cognition to lead to better learning. Still, among these studies none was conducted on the learning of formulaic sequences in a classroom setting. This thesis attempted to fill these gaps. Two studies were carried out at different points of time, on two different samples at similar low proficiency levels in Vietnam. The first study investigated the relative effectiveness of varying (cognitive based) teaching approaches on the learning of formulaic sequences. Sixty-nine formulaic sequences occurring in a coursebook were selected for the study. The participants were 60 university students. Learning was measured by two multiple-choice tests of receptive knowledge of form and meaning. Findings indicated that explicit teaching combined with incidental exposure to formulaic sequences in the coursebook was superior to the traditional coursebook instruction approach. Further, the results from explicit instruction with context sentences did not differ significantly from those of instruction without context. The second study employed a mixed methods quasi-experimental design to investigate whether the principled integration of motivational strategies and mental imagery (i.e. visionary techniques) could enhance the explicit vocabulary teaching approach that was effectively used in the first study. The findings indicated that deliberate and systematic employment of motivational techniques could facilitate the (effective) cognitive methods in terms of increasing the learning of receptive knowledge of form and meaning of target formulaic sequences, and that the novel visionary techniques were superior to the traditional motivational strategies. The deeper level of engagement associated with mental imagery was corroborated by a delayed posttest. In short, the findings of the first study presented in this thesis first underscores the superiority of the cognitive approach that used the systematic manipulation of explicit learning mechanisms to foster vocabulary acquisition. More importantly, it is revealed in the second study that the principled integration of motivational influences, especially the visionary techniques, can increase the effectiveness of the systematic explicit vocabulary instruction. Further research is needed though to confirm the findings of this study in different contexts.